2006
DOI: 10.1080/13538320600916668
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Research and Teaching Evaluation in Universities: Comparing an Italian and a Dutch case

Abstract: This article focuses on the impact of research and education evaluation on two universities: Trento State University (Italy) and the University of Amsterdam (The Netherlands). The article adopts a system approach to evaluation and proposes a model to describe and analyse evaluation systems. The analysis has been carried out by means of in-depth interviews with key decision-makers involved in the two universities. The analysis shows that many of the differences in impact can be linked to the different 'evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…The impacts were observed on three levels: micro-level of the personnel (students, academics), mezzo-level of the organisational units (departments, faculties), macro-level of the system units (HEI system, national system of education); in focus on three areas: rewards, adjusting policies and structures, higher education culture changes. On the other hand, the particular components implied in the content of the term of quality assurance have not the same impact on the quality education (Minelli, Rebora & Huisman, 2006). As different research results have shown, the measure of their impact varies.…”
Section: Methodology Of Research General Backgroundmentioning
confidence: 92%
See 1 more Smart Citation
“…The impacts were observed on three levels: micro-level of the personnel (students, academics), mezzo-level of the organisational units (departments, faculties), macro-level of the system units (HEI system, national system of education); in focus on three areas: rewards, adjusting policies and structures, higher education culture changes. On the other hand, the particular components implied in the content of the term of quality assurance have not the same impact on the quality education (Minelli, Rebora & Huisman, 2006). As different research results have shown, the measure of their impact varies.…”
Section: Methodology Of Research General Backgroundmentioning
confidence: 92%
“…As a tool of the self-assessment of teachers in connection to teacher evaluation within the internal quality assurance system introduced at Constantine the Philosopher University in Nitra A 15 Lukáčová D., Hašková A. Methodology of teacher selfassessment and its use in quality management.…”
Section: Instruments and Proceduresmentioning
confidence: 99%
“…A similar view resulted from a comparative study of Dutch and Italian institutional responses to external processes (Minelli et al, 2006). The two very different national and organisational backgrounds nonetheless resulted in a positive vision of how evaluation can contribute to the change process in universities.…”
Section: Impact Of Quality Assurancementioning
confidence: 89%
“…It is no coincidence that each period started with a legislative measure since in a system like the Italian one, with its hegemonic administrative paradigm, the law is an inevitable expression of administrative action (Capano 2003, p. 786). The official conception of evaluation deduced from these laws is analysed as are the evaluation techniques employed, the characteristics of evaluation bodies and the impact of evaluation in universities, based on the conviction that the systemic nature of evaluation (Minelli et al 2006) requires multifaceted investigation.…”
Section: Evaluation In the Italian University Systemmentioning
confidence: 99%